New physics for the twenty-first century - Fraser, Gordon (New York, Cambridge University Press, 2006)
Underpinning all the other branches of science, physics affects the way we live our lives, and ultimately how life itself functions. Recent scientific advances have led to dramatic reassessment of our understanding of the world around us, and made a significant impact on our lifestyle. In this book, leading international experts, including Nobel prize winners, explore the frontiers of modern physics, from the particles inside an atom to the stars that make up a galaxy, from nano-engineering and brain research to high-speed data networks. Revealing how physics plays a vital role in what we see around us, this book will fascinate scientists of all disciplines, and anyone wanting to know more about the world of physics today.
Bibliographical references 528-531p.; Index 532-548p.